Comparing membrane and spacer biofouling by Gram-negative Pseudomonas aeruginosa and Gram-positive Anoxybacillus sp. in forward osmosis. Issue 1 (2nd January 2019) - Bogler, Anne; Rice, Douglas; Perreault, Francois; Bar-Zeev, Edo
Abstract: Bacteria of different Gram-types have inherently different outer cell structures, influencing cell surface properties and bacterial attachment. Dynamic biofouling experiments were conducted over four days in a bench-scale forward osmosis (FO) system with Gram-negative Pseudomonas aeruginosa or Gram-positive Anoxybacillus sp. Biofouling resulted in ∼10% decline in FO permeate water flux and was found to be significant for Anoxybacillus sp. but not for P. aeruginosa . Additionally, a stronger permeate water flux decline for P. aeruginosa in experiments with a superhydrophilic feed spacer demonstrated that mitigation methods require testing with different bacterial Gram-types. It was found that although permeate water flux decline can be affected by bacterial Gram-type the stable performance under enhanced biofouling conditions highlights the potential of FO for wastewater reclamation.